Disruptive infrared image sensors enabled by quantum dots. Issue 4 (3rd October 2022) - Malinowski, Paweł E.; Lee, Jiwon; Georgitzikis, Epimitheas; Pejovic, Vladimir; Lieberman, Itai; Kim, Joo‐Hyoung; Lim, Myung‐Jin; Uytterhoeven, Griet; Moreno Hagelsieb, Luis; Ke, Tung Huei; Li, Yunlong; Puybaret, Renaud; et al.
Abstract: Sensors based on quantum dot photodiodes promise quality and accessibility improvement of infrared imaging. We demonstrate miniaturization by sub‐2‐μm pixel pitch arrays. Functionality is confirmed with external quantum efficiencies above 40% at 1450 nm. Monolithic integration enables high throughput and wide deployment of short‐wave infrared (SWIR) imagers in applications that previously could not afford them. Abstract : Sensors based on quantum dot photodiodes promise quality and accessibility improvement of infrared imaging. We demonstrate miniaturization by sub‐2‐μm pixel pitch arrays. Functionality is confirmed with external quantum efficiencies above 40% at 1450 nm. Monolithic integration enables high throughput and wide deployment of short‐wave infrared (SWIR) imagers in applications that previously could not afford them.